Mix Design of Ambient Cured Geopolymer Concrete with Fly Ash, GGBFS, and Borax - Hanani, Eklisia; Satyarno, Iman; Sulistyo, Djoko (Universitas Negeri Yogyakarta, 2024)
Geopolymer cement, using fly ash (FA), presents a viable alternative to Portland cement. However, FA-based geopolymers often lack reactivity and strength, necessitating combination with calcium-rich materials like ground granulated blast furnace slag (GGBFS). However, GGBFS could accelerate setting and decrease workability, requiring a retarder. Borax is recognized for its retarding properties in FA-based geopolymers, but its impact in FA-GGBFS systems remains understudied. This study evaluated the influence of varying proportions of FA and GGBFS with the addition of borax, on the setting time, workability, and mechanical strength of the geopolymer paste, mortar, and concrete under ambient curing conditions. Setting time test was conducted for the geopolymer paste, flow table test for workability assessment of mortar, and compressive strength testing at 1, 7, and 28 days for the mechanical strength of paste and concrete. Various FA:GGBFS ratios (100:0, 70:30, 50:50, and 0:100) were examined. Alkali activator consists of NaOH and Na2SO3 with Na2SO3/NaOH ratio (R) of 1.5 and alkali to precursors ratio (A) of 0.45 was used. Borax was added at a constant 3% by weight of the precursors. Both the volume ratios of paste to fine aggregate voids (Rm) and mortar to coarse aggregate voids (Rb) were set to 1.5. Borax increased initial setting time by 7-33 minutes for FA-GGBFS geopolymer. GGBFS replacement decreased the workability of mortar, with flow index ranging from 83-158%. Increasing GGBFS content significantly improved compressive strength in both paste and concrete samples. Notably, 100% GGBFS replacement yielded the highest concrete strength at 74.86 MPa after 28 days. However, the optimal balance of properties was achieved with a 50% GGBFS replacement, resulting in satisfactory strengths of 100.29 MPa for paste and 69.08 MPa for concrete, along with a 40-minute initial setting time and a flow index of 138%. These findings surpass prior studies on similar geopolymers.